The Models of Distance Forms of Learning in National Academy of Statistics, Accounting and Audit - Deryhlazov, L. V.; Kukharenko, V. M.; Perkhun, L. P.; Tovmachenko, N. M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Finding solutions to the problems faced by the Ukrainian education system require an adequate organizing structure for education system, enabling for transition to the principle of life-long education. The best option for this is the distance learning systems (DLS), which are considered by leading Ukrainian universities as high-performance information technologies in modern education, envisaged by the National Informatization Program, with the goals of reforming higher education in Ukraine in the context of joining the European educational area. The experience of implementing DLS “Prometheus” and Moodle and the main directions of distance learning development at the National Academy of Statistics, Accounting and Audit (NASAA) are analyzed and summed up. The emphasis is made on the need to improve the skills of teachers with use of open distance courses and gradual preparation of students for the learning process in the new conditions. The structure of distance courses for different forms of education (full-time, part-time, and blended) is built. The forms of learning (face-to-face, the driver complementary, rotation model; flex model, etc.) are analyzed. The dynamic version of implementing blended learning models in NASAA using DLS “Prometheus” and Moodle is presented. It is concluded that the experience of NASAA shows that the blended form of distance learning based on Moodle platform is the most adequate to the requirements of Ukraine’s development within the framework of European education.